PEMBERDAYAAN MASYARAKAT DALAM TATA KELOLA PARIWISATA DI KAMPUNG WISATA DEWO BRONTO YOGYAKARTA - Rumsari Hadi Sumarto; Lukas Dwiantara (Journal Publicuho, 2019)
This study aims to describe and analyze community empowerment activities in the Dewo Bronto Tourism Village in Yogyakarta through the concept of Community-Based Tourism. This study uses qualitative research that describes community empowerment through the concept of Community Based Tourism objectively based on data findings in the field. Data collection techniques using observation, interviews, and documentation. Community empowerment in the field of tourism in the tourism village is carried out through various fields such as culinary business, the production of natural dyes of batik, batik training, transportation, arts and cultural attractions. This effort can support the development of tourism in the Dewo Bronto Tourism Village. However, community empowerment needs to be supported by the ability of the community to create a brand for a tourist village so that the Tourism Village is better known by tourists. In the future, it is necessary to do research on millennial communities who are familiar with the digital world so that they can promote the Village Tourism digitally. The impact of the tourist village is better known to tourists globally